EXPRESII ALE TRADI܉IONALISMULUI ÎN POEZIA ROMÂNEASCĂ INTERBELICĂ - Plăcintă, Nina (CEP USM, 2017)
The object of the research are: to analyse the main directions of the inter-war Romanian traditionalism in its first period. The newness and scientific originality of the work consists of interpretation of the literary work not only from thematic point of view, but also from structural point of view.
Keywords: tradiționalismul interbelic; sămănătorismul; poporanismul; gândirismul